Dari Tradisi Menuju Inovasi: Literatur Review tentang Pengolahan Garam dan Potensi Replikasinya di Jembrana - Nugraha, I Made Aditya; Budiadnyani, I Gusti Ayu; Khairunnisa, Anis; Cesrany, Mahaldika; Utami, Diah Ayu Satyari (Jurnal Perikanan Unram, 2025)
Salt is a strategic commodity that plays an important role in daily life, both as food, industrial raw materials, and in the health sector. Salt processing in Indonesia, especially in coastal areas, is generally carried out traditionally, which includes evaporation and boiling techniques. However, traditional salt processing in many areas, including Jembrana, Bali, still faces challenges related to product quality, production efficiency, and limited market access. Innovations in salt processing technology, such as the use of geomembranes and salt houses, have been shown to improve the quality and quantity of salt production. This article aims to review the literature related to traditional and innovative salt processing, and explore the potential for replicating these innovations in Jembrana. The results of the study indicate that Jembrana has great potential to develop an innovation-based salt industry, by adopting the latest technology and strengthening community-based business institutions. However, several gaps in technology, human resources, and institutions must be addressed to create a sustainable and competitive salt industry. With support from various parties, including the government, academics, and local communities, Jembrana has the opportunity to become a leading region in the production of high-quality local salt.